The Development of Option Market and The Role of Indonesia Financial Service Au-thority (OJK) In Indonesia Capital Market Period 2004-2019 - Tinjung Desy Nursanti (Indonesia Banking School, 2019)
The purpose of this paper is to describe several things related to the notion of options, stock options, transaction mechanisms, applicable legislation based on the study of literature, the previous research, and various information from financial sites related to the topic mentioned above. Therefore, the research questions that needs to be answered are as follows: 1. What are the developments in options markets in Indonesia? 2. What is the role of the Financial Services Authority (OJK) in developing options trading transactions related to the legal aspect in Indonesia Stock Exchange or capital market? Meanwhile, option is basically a contract between two parties that contains the right for the option buyer to buy or sell the underlying asset of the contract at the certain time and price agreed upon at the beginning of the contract. The discussion will be emphasized on the development of derivative transactions and the role of Financial Services Authority (OJK) in increasing the number of derivative transactions in Indonesia period 2004-2019 regarding the change of legal aspect.